Survei Perilaku Agresif pada Siswa SMP Se Kecamatan Sindue - Putra, Rian Pratama; Nurwahyuni, Nurwahyuni; Ratu, Bau; Fitriani, Dian; Elfira, Ninil (Indonesian Journal of Counseling and Development, 2024)
Aggressive behavior in adolescents has become a serious problem in Indonesia, with data showing a significant increase in recent years. This study aims to reveal the picture of aggressive behavior of students in Junior High Schools (SMP) in Sindue District. Using a descriptive quantitative method, this study involved 524 eighth grade students from five SMPs selected through proportional random sampling. Data collection was conducted using a Likert scale instrument with 22 items, supported by interviews and documentation. The results showed that the scores of students' aggressive behavior were in the high category in all schools studied. The forms of aggressive behavior identified included verbal aggression (insulting, swearing), physical aggression (hitting, fighting), and destruction of school facilities. This study found five main characteristics of aggressive behavior: attacking behavior, unwanted behavior by the target, violation of social norms, hostility, and learned/imitated behavior. In conclusion, the high level of aggressive behavior among junior high school students requires immediate intervention through programs such as counseling, anger management, and social skills training, as well as active involvement from schools, parents, and mental health professionals.